2003
DOI: 10.4049/jimmunol.171.3.1224
|View full text |Cite
|
Sign up to set email alerts
|

Theileria parva-Transformed T Cells Show Enhanced Resistance to Fas/Fas Ligand-Induced Apoptosis

Abstract: Lymphocyte homeostasis is regulated by mechanisms that control lymphocyte proliferation and apoptosis. Activation-induced cell death is mediated by the expression of death ligands and receptors, which, when triggered, activate an apoptotic cascade. Bovine T cells transformed by the intracellular parasite Theileria parva proliferate in an uncontrolled manner and undergo clonal expansion. They constitutively express the death receptor Fas and its ligand, FasL but do not undergo apoptosis. Upon elimination of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 68 publications
0
46
1
Order By: Relevance
“…Additionally, it should be noted that the requirement of Akt kinase to support c-FLIP s expression may differ depending on the cell type and its activation state. Recently, Kuenzi et al 43 reported that the PI3K inhibitor LY did not downregulate c-FLIP expression in T cells of bovine origin transformed by Theileria parva parasite infection. These results indicate that Akt kinase can regulate Fas-mediated apoptotic signaling in a differential and cell/signaling context-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it should be noted that the requirement of Akt kinase to support c-FLIP s expression may differ depending on the cell type and its activation state. Recently, Kuenzi et al 43 reported that the PI3K inhibitor LY did not downregulate c-FLIP expression in T cells of bovine origin transformed by Theileria parva parasite infection. These results indicate that Akt kinase can regulate Fas-mediated apoptotic signaling in a differential and cell/signaling context-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, survival of a significant proportion of infected lymphocytes has been ascribed to the parasite permanently activating the NF-kB signalling pathway, probably through physical association with the IkB-signalosome (Heussler et al, 2002), but the actual mechanism of NF-kB-mediated protection remains elusive. Nonetheless, it is clear that the presence of live intracellular parasites leads to constitutive induction of a number of antiapoptotic proteins (Kuenzi et al, 2003) and a decrease in proapoptotic ones (Guergnon et al, 2003a), suggesting that Theileria somehow alters the balance of these key regulators in favour of survival. Infected lymphocytes also use autocrine loops to augment their proliferation and we have shown that a TNF-autocrine loop contributes to NF-kB activation, yet inhibition of TNF did not provoke apoptosis (Guergnon et al, 2003a).…”
Section: Introductionmentioning
confidence: 99%
“…Immunoblot analysis was performed according to standard procedures essentially as described [30]. Nitrocellulose membranes were blocked and incubated overnight at 4°C with specific primary Ab diluted in blocking buffer (5% BSA in TBS-Tween): anti-PKB 1:1000; anti-Phospho-PKB (Ser473) 1:1000; anti-ERK1/2 1:2000; anti-Phospho-ERK1/2 (Thr202/Tyr204) 1:1000; anti-AIF 1:2000; antiPhospho-p53 (Ser15) 1:2000 (all rabbit polyclonal); mouse monoclonal anti-p53 1:1000 (all Cell Signaling Technology, Beverly, MA, USA); goat polyclonal anti-Actin 1:4000 (Santa Cruz Biotechnology, Santa Cruz, CA, USA).…”
Section: Western Blotmentioning
confidence: 99%
“…To detect caspase activation, staining with FITC-valylalanyl-aspartic acid fluoromethyl ketone (FITC-VAD-fmk; Promega) was carried out as described [30]. Annexin V staining of exposed membrane phosphatidylserine was carried out using the Annexin V assay kit (Roche Diagnostics, Rotkreuz, Switzerland) following the manufacturer's protocol.…”
Section: Flow Cytometry and Measurement Of Membrane Potentialmentioning
confidence: 99%